Malayalam, a linguistic description - Prabodhachandran Nayar, V. R., 1938- (National Research Pub. Co., 1973)
Linguistic analysis of Krṣṇagātha, Malayalam verse work by Ceruśśeri, 15th century Malayalam poet.